A comparative study of plume rise formulae - PADMANABHAMURTY, B.; GUPTA, R. N. (MAUSAM, 1980)
A comparative study of plume rise formulae by Briggs, Tennesse Valley Authority, Holland, Lucas, Morton, et al. CONCAWE and whaley was made and it was found that slightly modified Lucas formulae appears to yield reasonable results under different stability and wind conditions.